Feature extraction of a sEMG in term of force - Jasni, Syazwan; Chong, Shin Horng; Yahya, Abu Bakar (2014)
This research will be at predicting force based on feature extraction of sEMG signal. The sEMG method is the placement of electrodes on the skin of muscle for the purpose to detect the electrical activity of the muscle. The purpose of predicting force is to help in the analysis in the development of prosthetic arms. The objectives of this research are to extract the features in time domain and to predict force by using simple linear regression technique. A group of 10 healthy people was chosen to determine the muscle condition during isometric condition. Long head biceps brachii is the muscles that will be analyzed to predict force. The force will be calculated based on the muscle model and will be used to evaluate the accuracy of force that is predicted from simple regression linear technique analysis.